A Systematic Review of Knowledge, Attitude and Practice towards Pharmacogenomics among Doctors - Mainul, Haque; Rohayah, Husain; Adamu, Ya’u (2015)
Background: Adverse drug events are public health problem that deserves special attention. The drug and its dosage can be tailored to the individual patient’s need and can solve many drug related problems if genetic factors are taken into account appropriately before initiating medications. Doctors are increasingly expected to integrate genomic medicine into routine patient care. The genomic incorporation yet not achieved public health expectations. This review analyses and summarises the various studies done on KAP towards pharmacogenomics. Methods: Fifteen KAP studies conducted on pharmacogenetics among doctors covered from 2004 to 2014 were selected. Studies conducted on doctors of different specialties were selected. This review exclude theoretical articles, studies done on general public; studies conducted on other healthcare professionals; and also studies conducted on genetics of diseases. Results: Knowledge and practice regarding pharmacogenetics among doctors were poor despite good attitudes. Several studies revealed factors that influence integration of pharmacogenetics into patient care with interventional recommendations. Conclusion: There is a critical need for additional training on pharmacogenomics among doctors and also to incorporate it into medical school curriculum. Emphasis should be placed on how to accurately interpret and critically evaluate the use, and safety of pharmacogenetic testing.